The Effect of Regional Financial Performance and Government Investment On Economic Growth In Yogyakarta Special Regency/City 2009-2019 - Jannah, Nanda Arif Faridhotul; Pangestuti, Dinik Fitri Rahajeng (Universitas Ahmad Dahlan, 2022)
Rapid and sustainable economic growth is an essential foundation for economic development sustainability. This research aims to examine the direct effect of variables on financial performance and government investment on economic growth in DIY. It was a quantitative study. The data were secondary data from five regional Yogyakarta from 2009 to 2019 obtained from the Central Statistics Agency. The data were analyzed using a regression model processed by SPSS 23. The result of the study showed that: 1) Financial performance used effectiveness ratio hasn't effect on economic growth in Yogyakarta; 2) Financial performance used efficiency ratio has no effect on economic growth in Yogyakarta; 3) Government investment has a negative effect on economic growth in Yogyakarta.